1998
DOI: 10.1111/j.1749-6632.1998.tb08932.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Routine Ultrasound Screening of Pregnancies in the Eurofetus Database

Abstract: In this prospective study, we recorded details on 3,685 fetuses with congenital structural abnormalities from an unselected population of women who underwent routine ultrasound examinations during their pregnancies. Overall, 2,262 fetuses were diagnosed as being abnormal before birth (sensitivity = 61.4%). The total number of abnormalities was 4,615, of which 1,733 (37.5%) were major abnormalities. The overall number of detected abnormalities was 2,593 (sensitivity = 56.2%). If only major abnormalities were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 8 publications
1
30
1
1
Order By: Relevance
“…Similarly, 68.5% of respondents did not know whether or not ultrasound could be used to diagnose any kind of abnormality. According to the Eurofetus study, the largest prospective study ever performed, the overall fetal detection rate for anomalous fetuses was 61.4% (14). In another study, the detection rate for significant abnormalities was found to be 55% (15).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, 68.5% of respondents did not know whether or not ultrasound could be used to diagnose any kind of abnormality. According to the Eurofetus study, the largest prospective study ever performed, the overall fetal detection rate for anomalous fetuses was 61.4% (14). In another study, the detection rate for significant abnormalities was found to be 55% (15).…”
Section: Discussionmentioning
confidence: 99%
“…Romosan et al (5), found that the detection rate of major malformations in chromosomally normal fetuses were 68% with a detection rate of 37% at <22 weeks, and the corresponding detection rates of chromosomally abnormal fetuses were 46% and 33%. These rates change according to the nature of the anomaly, as it is highest for malformations in the central nervous and genito-urinary systems, and lowest for malformations of skeletal and circulatory systems (5,6).…”
Section: Discussionmentioning
confidence: 99%
“…abnormalities that have implications for the infant's health) and 46% of the minor abnormalities (i.e. abnormalities that have no implications for the infant's health) [6,12].…”
Section: Developments In Fetal Ultrasoundmentioning
confidence: 99%